TANGGUNG JAWAB NOTARIS ATAS AKTA PERNYATAAN KEPUTUSAN RAPAT - Jonathan Adi Biran Munandir; Thohir Luth (University of Merdeka Malang, 2017)
The authority and responsibility of the notary on the deed of Statement of Meeting Decision and to analyze the strength of notary proof of the deed of Statement of Meeting Decision. The method used in this research is normative law research with approach method of legislation. The primary, secondary and tertiary law materials obtained by the authors will be analyzed by using literature techniques using grammatical and logical legal interpretations. The result of research with the above method indicates that Notary of Notary's responsibility to Statement of Meeting Decision is only responsible only for formal truth, while the truth of the contents of the deed is the responsibility of the parties to the notary because the notary does not know and attend the meeting. The Declaration of Decision of the Meeting includes the evidence of letters and including the